Pemetaan Rumah Sehat berdasarkan Faktor Kesehatan Lingkungan di Dukuh Sumuran, Palbapang, Bantul - Maghfiroh, Dessy Lailatul; Rosadianty, Debriela Salvarina; Tullazulfa, Fadila; N. Putri, Ajeng Ramadanti; Rois, Ibnu (Jurnal Abdimas Kesehatan (JAK), 2024)
A map is a representation of the earth's surface reduced to two dimensions, allowing efficient observation of the extent of the earth. Thematic maps present specific data in relation to specific topography. Remote sensing uses technology for processing data without direct contact with objects. The GPS Essential and ArcGIS applications help in creating distribution maps, providing way points with GPS Essential makes it easier to determine locations accurately. In the world of environmental health, mapping activities in the work area of the Bantul I Community Health Center are needed to produce mapping of the health status of homes and make it easier for sanitarians to take action. By having a map of the health status distribution of houses in Dukuh Sumuran, Palbapang Village, Kapanewon Bantul, Bantul Regency, it can make it easier for sanitarian employees to take further action regarding health problems in Dukuh Sumuran, Palbapang, Bantul, Bantul Regency. The aim and benefits of this remote sensing activity are to collect data about natural resources and their surroundings such as the distribution of healthy houses in Sumuran Hamlet which is obtained in relation to the type of clean water facilities, type of family latrines, waste water disposal facilities, waste management, the presence of larvae and history of diseases such as ISPA, dengue fever, diarrhea and other diseases. The method used in this activity is observation and interviews followed by analysis in the form of a spatial map with the ArcGis application and determining coordinate points with essential GPS. From this activity, it can be concluded that there are 81 healthy houses and 19 less healthy houses in the target area. There are houses that do not have sanitation facilities (latrine and SPAL) and several components of a healthy house do not meet the requirements.